Yemen: the challenge of delivering aid in an active conflict zone - Ann Marie Kimball; Aisha Jumaan (Taylor & Francis Group, 2020)
Introduction: In March 2015 a Saudi-led coalition began an air campaign and ground offensive in Yemen. The conflict has resulted in at least 100,000 people killed and 3.2 million people internally displaced. Over the last 29 months of the war, the Yemen Relief and Reconstruction Foundation (YRRF), working through an informal network of indigenous volunteers, has successfully provided food, clothing, medicine and water filters to areas under siege. Context: Asymmetric warfare complicates humanitarian assistance. YRRF succeeds through an informal network: hundreds of Yemeni volunteers negotiating passage through competing armed checkpoints focussed on concrete, lifesaving action. Method: A case-study report about a local, informal, Yemeni-led relief organisation supported by remote financing and training. Findings: YRRF has succeeded in delivering food and clothing to more than 20,000 families, distributing more than 1200 water filters to remote villages and internally displaced families and medicine to five cancer centres. Innovative contribution: Yemen has multiple combatants within its territory, with competing systems for aid distribution and healthcare delivery. YRRF has developed an efficient and cost-effective technique for managing those complex environments while delivering care to fragile, and often displaced, populations in a war zone. Dynamic networks: local volunteers, working with local leaders, understanding culutral aspects, in country office, staying aploitical and meeting the needs of the population are key.